Free ternary semicommutative groupoids - Celakoska-Jordanova, Vesna (Faculty of Mathematics and Natural Sciences, South-West University "Neofit Rilsky", Blagoevgrad, Bulgaria, 2013)
Free objects in the variety V of ternary groupoids defined by the identity [xyz] = [zyx] , are described. A proper characterization of the class of V -free objects by means of the class of V -injective groupoids is obtained as well.
Keywords: ternary semicommutative groupoid, free/injective ternary semicommutative groupoid.